SARS-CoV-2 receptor ACE2-dependent implications on the cardiovascular system: From basic science to clinical implications - Groß, Sonja; Jahn, Christopher; Cushman, Sarah; Bär, Christian; Thum, Thomas (Journal of molecular and cellular cardiology, 2020)
The current COVID-19 pandemic started several months ago and is still exponentially growing in most parts of the world – this is the most recent and alarming update. COVID-19 requires the collaboration of nearly 200 countries to curb the spread of SARS-CoV-2 while gaining time to explore and improve treatment options especially for cardiovascular disease (CVD) and immunocompromised patients, who appear to be at high-risk to die from cardiopulmonary failure. Currently unanswered questions are why elderly people, particularly those with pre-existing comorbidities seem to exhibit higher mortality rates after SARS-CoV-2 infection and whether intensive care becomes indispensable for these patients to prevent multi-organ failure and sudden death. To face these challenges, we here summarize the molecular insights into viral infection mechanisms and implications for cardiovascular disease. Since the infection starts in the upper respiratory system, first flu-like symptoms develop that spread throughout the body. The wide range of affected organs is presumably based on the common expression of the major SARS-CoV-2 entry-receptor angiotensin-converting enzyme 2 (ACE2). Physiologically, ACE2 degrades angiotensin II, the master regulator of the renin-angiotensin-aldosterone system (RAAS), thereby converting it into vasodilatory molecules, which have well-documented cardio-protective effects. Thus, RAAS inhibitors, which may increase the expression levels of ACE2, are commonly used for the treatment of hypertension and CVD. This, and the fact that SARS-CoV-2 hijacks ACE2 for cell-entry, have spurred controversial discussions on the role of ACE2 in COVID-19 patients. In this review, we highlight the state-of-the-art knowledge on SARS-CoV-2-dependent mechanisms and the potential interaction with ACE2 expression and cell surface localization. We aim to provide a list of potential treatment options and a better understanding of why CVD is a high risk factor for COVID-19 susceptibility and further discuss the acute as well as long-term cardiac consequences. [Display omitted] •COVID-19 patients with underlying CVD have drastically increased risks of mortality.•SARS-CoV2 uses ACE2 as cell entry receptor.•Current and novel COVID-19 drugs may act on the SARS-CoV-2 receptor ACE2.•ACE-I and ARB may interfere with COVID-19 susceptibility and effects on the heart.